Labour market status of job seekers in regional matching processes - Sanna-Mari Hynninen (European Regional Science Association (ERSA), 2005)
This study examines the matching aspects of local labour markets focusing on the status of job seekers in the matching process, on spatial autocorrelation in labour market conditions of local labour markets, and on differences in matching processes between areas with permanently deviating unemployment rates. The data set is temporally, spatially, and by labour market positions of job seekers highly disaggregate monthly data from 171 Local Labour Offices (LLOs) in Finland over 12 years. According to the results, an increase in the share of long-term unemployed job seekers decreases matches, and an increase in the share of job seekers out of labour force increases successful matches in local labour markets. The matching process does not work in the same way in all areas, but on the contrary its functioning is dependent on the unemployment conditions. Effects of increases in the number of inputs on successful matches depend on the proportional share of that input in the area as well as on the composition of the stock of job seekers. The results also indicate the labour market conditions and matching processes across neighbouring LLOs being spatially autocorrelated.
Keywords: 330